Penggunaan Pantun dalam Komunikasi Politik: Studi Kasus Kampanye & Debat Pilgub Jakarta 2024-2029 - Umam, Akhmad Hairul; Setyawan, Irwan; Khopipah, Siti (Universitas Tribhuwana Tunggadewi, 2024)
This study examines the use of pantun in political communication during the Jakarta gubernatorial campaign and debate for the 2024-2029 election. Pantun, a form of traditional poetry deeply rooted in Indonesian culture, is frequently utilized as a political communication tool, allowing candidates to convey messages in a subtle, entertaining, and educational manner. The focus of this study is to analyze the communication styles of the gubernatorial candidates through the use of pantun in public debates, along with examining its impact on the audience. This research employs a qualitative approach using discourse analysis methods to identify patterns and themes of pantun usage throughout the campaign and debate. The findings reveal that pantun serves not only as a rhetorical tool for diplomatically conveying both criticism and praise but also as an effective means of building rapport with the audience. Moreover, pantun strengthens the candidates' public image, showcasing their cultural affinity and creativity, which resonates with Indonesian voters and enhances their political appeal.Penelitian ini mengkaji penggunaan pantun dalam komunikasi politik selama kampanye dan debat pemilihan gubernur Jakarta periode 2024-2029. Pantun, sebagai salah satu bentuk puisi tradisional yang mengakar kuat dalam budaya Indonesia, sering dimanfaatkan sebagai alat komunikasi politik yang memungkinkan para kandidat menyampaikan pesan secara halus, menghibur, dan edukatif. Fokus penelitian ini adalah menganalisis gaya komunikasi para kandidat gubernur melalui penggunaan pantun dalam debat publik serta dampaknya terhadap audiens. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis wacana untuk mengidentifikasi pola dan tema penggunaan pantun dalam kampanye dan debat. Hasil penelitian menunjukkan bahwa pantun tidak hanya berfungsi sebagai alat retorika untuk menyampaikan kritik dan pujian secara diplomatis, tetapi juga menjadi cara yang efektif dalam membangun kedekatan dengan audiens. Selain itu, pantun memperkuat citra publik para kandidat, menampilkan kedekatan mereka dengan budaya dan kreativitas yang dimiliki, sehingga meningkatkan daya tarik politik mereka di mata pemilih Indonesia.